1973
DOI: 10.1530/jrf.0.0340543
|View full text |Cite
|
Sign up to set email alerts
|

A Re-Examination of the Role of Phospholipids as Energy Substrates During Incubation of Ram Spermatozoa

Abstract: Lardy & Phillips (1941a,b) postulated that the endogenous phospholipids are used as a source of oxidizable energy by bull spermatozoa in the absence of sugar. Their results were not confirmed by the later work of Bomstein & Steberl (1957) with bull spermatozoa, or by with human spermatozoa. Hartree & Mann (1959, 1961 examined the effect of aerobic and anaerobic incubation of washed ram spermatozoa on the utilization of endogenous phospholipids and their results, though different from those of Lardy & Phillip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1976
1976
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…In fact, back in the 1960s, some authors claimed to show that different mammalian sperm oxidize [1-14 C] fatty acids, as indicated by the production of labeled CO 2 (58,59). However, conflicting data were subsequently published (60,61). In any case, all these experiments were performed with washed sperm (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, back in the 1960s, some authors claimed to show that different mammalian sperm oxidize [1-14 C] fatty acids, as indicated by the production of labeled CO 2 (58,59). However, conflicting data were subsequently published (60,61). In any case, all these experiments were performed with washed sperm (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, since acetylcarnitine has been proposed as an energy source for rabbit spermatozoa as they traverse the epididymis (Storey & Keyhani, 1974), we have measured the levels of this compound in rabbit epididymal tissues. The idea proposed by Lardy & Phillips (1941a, b) that endogenous phospholipids serve as an energy source for spermatozoa as they traverse the epididymis is generally accepted but has been recently questioned (Darin-Bennett, Poulos & White, 1973;Storey & Keyhani, 1974). Storey & Keyhani (1974) have reported that the mitochondria of rabbit epididymal spermatozoa lack type I carnitine palmitoyl transferase and hence are unable to oxidize long-chain fatty acids.…”
Section: Introductionmentioning
confidence: 99%
“…Sphingomyelin, phosphatidyl serine, cardiolipin and plasmalogen were reported to be absent in buffalo semen by Guraya & Sidhu (1975), but their occurrence is definitely established by the present study. Among the lysophospholipids, the choline form has been reported in bull, ram and boar semen (Clegg & Foote, 1973;Darin-Bennett et al, 1973;Johnson et al, 1969) but Jain & Anand (1975b) detected, in addition, the ethanolamine and serine forms in the phospholipids of goat semen. As in the goat, there was more lysophosphatidyl choline and ethanolamine than serine in buffalo and bull seminal phospholipids.…”
Section: Phospholipidsmentioning
confidence: 99%